Efficient optimal power flow learning: A deep reinforcement learning with physics-driven critic model - Ahmed Sayed; Khaled Al Jaafari; Xian Zhang; Hatem Zeineldin; Ahmed Al-Durra; Guibin Wang; Ehab Elsaadany (International Journal of Electrical Power & Energy Systems)
The transition to decarbonized energy systems presents significant operational challenges due to increased uncertainties and complex dynamics. Deep reinforcement learning (DRL) has emerged as a powerful tool for optimizing power system operations. However, most existing DRL approaches rely on approximated data-driven critic networks, requiring numerous risky interactions to explore the environment and often facing estimation errors. To address these limitations, this paper proposes an efficient DRL algorithm with a physics-driven critic model, namely a differentiable holomorphic embedding load flow model (D-HELM). This approach enables accurate policy gradient computation through a differentiable loss function based on system states of realized uncertainties, simplifying both the replay buffer and the learning process. By leveraging continuation power flow principles, D-HELM ensures operable, feasible solutions while accelerating gradient steps through simple matrix operations. Simulation results across various test systems demonstrate the computational superiority of the proposed approach, outperforming state-of-the-art DRL algorithms during training and model-based solvers in online operations. This work represents a potential breakthrough in real-time energy system operations, with extensions to security-constrained decision-making, voltage control, unit commitment, and multi-energy systems.